Nigerian Public Enterprise Privatization and Commercialization: Issues and Prospects - Sa’ad , Abdulmumin; Ayilara, Nasir Olarewaju (Kashere Journal of Politics and International Relations, 2024)
The paper explores the difficulties or issues associated with the privatization and commercialization of public firms in Nigeria, as well as potential solutions. Privatization and commercialization are essential strategies for a nation's economic development, especially in emerging nations like Nigeria. The primary performance of Nigeria's public companies has devolved into an illusion, and this has led to policy recommendations on the best ways to rescue them from their plight. There are too many issues with this privatization and commercialization initiative of public enterprises to list them all, though. This essay examines Nigeria's privatization and commercialization. The goals, difficulties, or issues associated with privatization and commercialization are also revealed. However, the study employs public choice theory and economic theory to analyze the discourse; to gather the required data, it uses secondary sources of data collection. Crucially, it also offered some direction on how to move forward with the successful privatization and commercialization of public companies in Nigeria. Promoting private initiatives that would establish market discipline, track performance, improve opportunities and accountability, and foster better management is the aim of privatizing and commercializing state-owned enterprises.